P03.01 Secondary central nervous system lymphoma (SCNSL) in patient with non Hodgkin lymphoma (NHL): a case report - Susanti, E (Neuro Oncol, 2019)
BACKGROUND: non Hodgkin lymphoma (NHL) is a systemic cancer that originates from lymphocites. Central nervous system lymphoma is a rare form of non Hodgkin lymphoma that involve brain parenchym and spinal cord. The most common type of nervous system involvement is a leptomeningeal metastases. Whereas brain metastases is an extremely rare finding in NHL. We present a case report of NHL patient which metastasized to brain parenchym. MATERIAL AND METHODS: Case report: a fourty two year old male patient suffered from seizure in September 2018, 7 days prior to hospitalized. severe headache and weakness on the left extremities were found in addition to seizure. A single nodule on the right frontal and another nodules on the right neck region were also found since 7 months ago. Patient was diagnosed with NHL in 2017 after a confirmed biopsy of NHL and underwent a chemotherapy procedure, but uncompleted. After head ct scan procedure in September 2018, which depicted a round mass in frontal lobe, patient underwent a complete chemotherapy procedure with CHOP regimen in September 2018. Another head ct scan was performed in January 2019 after a completed chemotherapy cycle which showed significant decrease in tumour size. RESULTS: before and after head ct scan showed significant decrease in tumour size, from 4cmx2cm before chemotherapy and 2.5cmx1.3cm after chemotherapy CONCLUSION: central nervous system involvement in NHL is a rare condition that carries a poor prognosis. Prophylaxis therapy still on debate about it’s efficacy to prevent this disease from spreading or relapse. Awareness of the possibility central nervous system involvement should always remain in a physician’s mind when dealing with NHL patients.